2022
DOI: 10.3390/jcm11113042
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ABO Blood Group Distribution and COVID-19 Infection in Patients Admitted to the ICU: A Multicenter Observational Spanish Study

Abstract: Since the beginning of the COVID-19 pandemic in December 2019, a relationship between the ABO blood group type and the novel coronavirus SARS-CoV-2, the etiological agent of COVID-19, has been reported, noting that individuals with the O blood group are the least likely to be infected. Spain is one of the most badly affected countries worldwide, with high rates of patients diagnosed, hospitalized, and deceased due to COVID-19 infection. The present study aimed to analyze the possible relationship of ABO in COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…Male donors were a median of 4 years older than female donors (42.0 vs. 37.9; p = 0.003). The distribution of donors' ABO blood type matched that of the Spanish population [14]: 44.6% group A, 39.4% group O, 8.8% group B and 7.2% group AB, with the commonest types being A positive (36.8%) and O positive (33.2%). Donors' COVID‐19 diagnosis was confirmed by RT‐PCR in 292 cases (73%).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Male donors were a median of 4 years older than female donors (42.0 vs. 37.9; p = 0.003). The distribution of donors' ABO blood type matched that of the Spanish population [14]: 44.6% group A, 39.4% group O, 8.8% group B and 7.2% group AB, with the commonest types being A positive (36.8%) and O positive (33.2%). Donors' COVID‐19 diagnosis was confirmed by RT‐PCR in 292 cases (73%).…”
Section: Resultsmentioning
confidence: 94%
“…Donors' COVID-19 severity was not recorded in the study protocol. Their median duration of symptoms of SARS-CoV-2 infection was 13 days (IQR [7][8][9][10][11][12][13][14][15][16][17][18][19], and it increased with donor age at a rate of 0.17 days for each year increase in donor age (95% CI, 0.09-0.25; p < 0.001). We did not find an association between symptom duration and donor sex or ABO blood type.…”
Section: Donors' Covid-19 Diagnosis Was Confirmed By Rt-pcr In 292 Casesmentioning
confidence: 99%
“…Blood group O individuals in Iraq were found to be less likely to develop SARS‐CoV‐2 than non‐O participants, while A type carriers showed a higher risk of infection 20 . The other investigation in Spain also showed that patients with blood group O presented a significantly lower risk for SARS‐CoV‐2 infection and hospitalization 21 . Furthermore, different studies found that subjects with Rh‐negative blood type were at lower risk of SARS‐CoV‐2 infection, severe form of the disease and mortality 11,16,22 .…”
Section: Discussionmentioning
confidence: 92%
“…20 The other investigation in Spain also showed that patients with blood group O presented a significantly lower risk for SARS-CoV-2 infection and hospitalization. 21 Furthermore, different studies found that subjects with Rh-negative blood type were at lower risk of SARS-CoV-2 infection, severe form of the disease and mortality. 11,16,22 In the context of the demonstrated data, ABOassociated differences in COVID-19 infection outcomes were explored in the present study as well as the humoral response to COVID-19 vaccine and long-term safety.…”
Section: Discussionmentioning
confidence: 99%
“…A 2018 study reported a higher mortality rate in severe trauma patients with O type blood compared to non-O peers, but did not show significantly increased RBC requirements within the first 24 hours after arrival to the emergency room. 3 More recently, the relationship between ABO blood group and influence on COVID-19 susceptibility and outcomes has piqued the interest of the scientific community, with observational studies concluding that the odds for COVID-19 infection were significantly increased for blood group A and decreased for blood group O, 17,18 reinforcing the idea that ABO phenotypes may affect a multitude of physiologic processes including innate immunity. In the cardiac surgical setting, the relationship between blood group and bleeding has been studied in several different populations, with conflicting results-several smallscale studies of LVAD patients have failed to demonstrate a difference in bleeding rates between O and non-O groups, [19][20][21] whereas Welsby et al found that in CABG patients, O blood group did not have increased blood loss and instead required fewer RBC transfusions intraoperatively compared to their non-O peers.…”
Section: Discussionmentioning
confidence: 99%